Assessment of the surface roughness and hardness of acrylic resin after incorporation of sodium fluoride salts (An In-vitro Study) (Mustansiria Dental Journal, 2023)
The control of oral hygiene is of great importance, particularly in dental work, to prevent caries caused by bacteria. One method to inhibit bacterial growth is usually by using fluoridated dental materials. The objectives are to assess the effect of sodium fluoride powder (NaF) inclusion with different concentrations on the surface roughness and hardness of heat-cured acrylic resins. A total of forty disc-shaped samples with a diameter of (12±0.1) mm and a thickness of (2±0.1) mm have been fabricated from heat cure acrylic resin. They were grouped into four subgroups according to different concentrations of NaF with 10 specimens for each group. Sodium fluoride powder (NaF) was incorporated into the monomer in concentrations of 0% (control group), 1%, 3%, and 5%. Then mixing was done with polymer according to manufacturer instructions and the conventional flasking, and packing procedures were used. Finally, the specimens are subjected to hardness and surface roughness tests. The results of this study revealed that the lowest mean value surface roughness (Ra) was with the (5%) group of NaF (7828). While, for the surface hardness test, the group (5%) of Naf showed the highest mean value among their subgroups (82.30).  According to the results of the current study, sodium fluoride powder (NaF) has a positive effect on both the surface roughness and hardness of acrylic resin.